Beckman P/ACE Capillary Electrophoresis System 2100 (1990)
Beckman introduced the P/ACE 2100 series of capillary electrophoresis systems in 1991. Electrophoresis uses an electric field to separate particles in a medium (like a gel) based on their size, charge, or a binding affinity.
Keywords: Medical laboratory technology; Scientific apparatus and instruments; Capillary electrophoresis; Beckman Instruments, Inc.